Berlitz German fast, effective way to all-around fluency. - 20160731 frey50; Learning Company (Cambridge, MA. : Learning Company, 1997)
Offers instruction in speaking, understanding, reading, and writing German. Users may practice conversational German using speech recognition feature and compare pronunciation to native speaker's with record/playback function.
Title from disc label.
Title on user's guide: Berlitz Spanish, French, German.
System requirements for Windows: IBM compatibles; 486DX/66MHz or better; Windows 95; 16MB RAM; Windows 3.1; 8MB RAM; hard drive; MS-DOS or PC-DOS version 5.0 or higher; 256-color SVGA; double speed CD-ROM drive; sound card; microphone; mouse.
System requirements for Macintosh: Power Mac/Power PC; hard drive; 16MB RAM; System 7.5.3 or higher; double-speed CD-ROM drive; 256-color display; microphone; mouse.
Keywords: German language -- Computer-assisted instruction for foreign speakers; German language -- Self-instruction